2022
DOI: 10.2169/internalmedicine.9065-21
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Types of Taste Disorders among Patients with COVID-19

Abstract: Objective Based on the increasing incidence of smell and taste dysfunction among coronavirus disease 2019 (COVID-19) patients, such issues have been considered an early symptom of infection. However, few studies have investigated the type of taste components that are most frequently affected in COVID-19 patients. This study investigated the difference in frequencies of the types of taste component disorders among hospitalized COVID-19 patients. Methods In this retrospective, single-center, observational study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…20 Dysgeusia in most of the COVID-19 patients may be the sole symptom at the time of presentation and of leads to diagnosis. 21 In a study conducted by Nanjo Y et al 22 has observed the prevalence of dysgeusia was 52.2%. This is consistent with my study's findings.…”
Section: Discussionmentioning
confidence: 97%
“…20 Dysgeusia in most of the COVID-19 patients may be the sole symptom at the time of presentation and of leads to diagnosis. 21 In a study conducted by Nanjo Y et al 22 has observed the prevalence of dysgeusia was 52.2%. This is consistent with my study's findings.…”
Section: Discussionmentioning
confidence: 97%
“…[15,29] In addition to that, salt or sweet level of taken food can be important for people with affected primary sense of taste or different taste disorders, which is very common in case of people with confirmed COVID-19. [30] The main contributions of this work can be summarized as follows:…”
Section: Discussionmentioning
confidence: 99%